2015
DOI: 10.1111/jth.12987
|View full text |Cite
|
Sign up to set email alerts
|

Systematic monitoring of hemostatic management in hemophilia A patients with inhibitor in the perioperative period using rotational thromboelastometry

Abstract: To cite this article: Furukawa S, Nogami K, Ogiwara K, Yada K, Minami H, Shima M. Systematic monitoring of hemostatic management in hemophilia A patients with inhibitor in the perioperative period using rotational thromboelastometry. J Thromb Haemost 2015; 13: 1279-84.Summary. Background: The management of hemophilia A (HA) patients with inhibitors on bypassing therapy remains challenging. In particular, the monitoring of treatment is restricted by the limited reliability and lack of standardization of current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 10 publications
3
49
0
Order By: Relevance
“…Other studies have shown that Plt counts and P‐selectin levels increase in the later phases of induction, and it may be that restoration of Plt function plays an important role in these overall mechanisms. Further studies are required to examine the interplay between plasma‐derived components and Plt by using whole blood global clotting assays, for example, rotational thromboelastometry (ROTEM ® ) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that Plt counts and P‐selectin levels increase in the later phases of induction, and it may be that restoration of Plt function plays an important role in these overall mechanisms. Further studies are required to examine the interplay between plasma‐derived components and Plt by using whole blood global clotting assays, for example, rotational thromboelastometry (ROTEM ® ) …”
Section: Discussionmentioning
confidence: 99%
“…The study population included consecutive newly diagnosed patients with ALL enrolled from August 2014 to March 2018 at four core hospitals for pediatric hematology and oncology in Japan. All patients received induction chemotherapy following the guidelines of either the Japan Association of Childhood Leukemia Study (JACLS) ALL-02 protocol, consisting of a total of six doses of Escherichia coli L-Asp (Leunase R , Kyowa Hakko Kirin Co., Ltd, Tokyo, Japan) 6000 U/m 2 (JACLS group, Day 15,17,19,22,24,and 26) or the Berlin-Frankfurt-Münster (BFM) 95 oriented protocol consisting of a total of eight doses of E. coli L-Asp (Leunase R ) 5000 U/m 2 (BFM group, Days 12,15,18,21,24,27,30, and 33) ( Figure 1). 14,15 Thromboprophylaxis including FFP transfusion, usually without cryoprecipitate because of it being an uncommon product in Japan, for low fibrinogen (Fbg) levels (≤50 mg/dL), AT supplementation for low AT levels (≤70% of control), and administration of Dana for anticoagulation was included in these protocols, if required, ultimately based on the decision of each clinician.…”
Section: Enrolled Patientsmentioning
confidence: 99%
“…Researchers have explored the use of global assays to measure coagulation potential with these products . Furthermore, evidence suggests that global assays are a useful tool to detect bleeding tendency in people with HA, might facilitate individualized treatment of patients with HA, and help monitor bypassing agents in patients with inhibitors …”
Section: Introductionmentioning
confidence: 99%
“…Figure a–c illustrates representative thromboelastograms during the bleeding phase. CT NATEM reflects the initiation phase of coagulation, and was markedly shortened compared with normal (936 s; 95%CI: 762–1,127 s), especially at BL day –1 (324 s) and BL day +1 (615 s). These data confirmed a hypercoagulant state at these times.…”
Section: Resultsmentioning
confidence: 96%
“…The coagulation process was assessed using the clotting time (CT NATEM ; the time until detection of clot firmness at 2 mm amplitude) and clot formation time (CFT; the time until detection of clot firmness of 20 mm amplitude; Fig. ) . Measurements were obtained up to a maximum of 3,600 s. The impact of TF derived from AML cells on clot formation was measured by the changes in CT NATEM with the ex vivo addition of anti‐TF monoclonal antibody (mAb; f.c., 50 μg/mL) during the bleeding phase.…”
Section: Methodsmentioning
confidence: 99%